2016
DOI: 10.1530/erc-15-0445
|View full text |Cite
|
Sign up to set email alerts
|

Recent incidences and differential trends of thyroid cancer in the USA

Abstract: The incidence rate of thyroid cancer has been rising rapidly in recent decades, but its trend remains unclear. To investigate this, we analyzed the database of SEER 13, 1992-2012 in USA, with a particular focus on conventional papillary thyroid cancer (CPTC) and follicular-variant PTC (FVPTC). Of the 75,992 thyroid cancers, 61.3% were CPTC, and 25.7% were FVPTC, and their incidence rates (IRs) were both significantly increased from 1992 to 2012 (P all <0.001), with CPTC being 2.4-time FVPTC (P<0.001) and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
126
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(132 citation statements)
references
References 19 publications
3
126
1
2
Order By: Relevance
“…This variation in actual RAI treatment given is consistent with the regional differences in an opinion on RAI treatment found in the cross-sectional survey by Sawka et al [7]. Variation in management cannot be attributed to variation in the distribution of well-differentiated thyroid cancer across T stage, as found in our study, it was similar between centers and to other studies [8]. …”
Section: Discussionsupporting
confidence: 91%
“…This variation in actual RAI treatment given is consistent with the regional differences in an opinion on RAI treatment found in the cross-sectional survey by Sawka et al [7]. Variation in management cannot be attributed to variation in the distribution of well-differentiated thyroid cancer across T stage, as found in our study, it was similar between centers and to other studies [8]. …”
Section: Discussionsupporting
confidence: 91%
“…DTC exhibits a lower mortality rate compared with other carcinomas, but certain types of DTC, such as radioiodine refractory differentiated thyroid carcinoma, are difficult to diagnose at an early stage (23,24). Patients with DTC have poor prognosis due to DM (25)(26)(27). Previous studies have indicated that LNM, tumor size, histologic subtype and ETE are risk factors that influence the prognosis of patients with DTC (20,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer is the most common malignant tumor of the endocrine system and the most common head and neck cancer. The incidence of thyroid cancer has increased significantly in the past two decades [1].…”
Section: Introductionmentioning
confidence: 99%